MAGOH and MAGOHB Knockdown in Melanoma Cells Decreases Nonsense-Mediated Decay Activity and Promotes Apoptosis via Upregulation of GADD45A - Söderberg, Agnes; Meißgeier, Tina; Boßerhoff, Anja Katrin; Linck-Paulus, Lisa (Cells, 2022)
Cutaneous malignant melanoma is a highly proliferative and aggressive skin cancer with a steadily increasing incidence and a low long-term survival rate after metastatic progression. The protein MAGOH and its highly identical homologue MAGOHB are core components of the exon junction complex (EJC), which regulates splicing, stability and translation of mRNAs. The EJC, and especially MAGOH, has been shown to be involved in the development and progression of several cancers. In melanoma, the expression and function of both homologues remain essentially unexplored. This study identifies high MAGOH and MAGOHB protein expression in cutaneous melanoma cell lines and patient derived tissue samples. An siRNA-mediated knockdown of MAGOH significantly inhibits melanoma cell proliferation. The loss of MAGOH does not affect cell cycle progression, but induces apoptosis, an effect that is enhanced by a simultaneous knockdown of MAGOH and MAGOHB. MAGOH and MAGOHB do not influence the expression of the pro-apoptotic protein Bcl-XS or exon skipping. However, the knockdown of MAGOH and MAGOHB strongly decreases nonsense-mediated decay (NMD) activity, leading to an upregulation of the pro-apoptotic protein GADD45A. In conclusion, simultaneous inhibition of MAGOH and MAGOHB expression substantially affects cell survival, indicating both MAGOH homologues as promising new targets for the treatment of melanoma.
CRIS-Team Scopus Importer:2022-12-23
Keywords: exon junction complex; GADD45A; MAGOH; melanoma; nonsense-mediated decay